2011
DOI: 10.1021/jf104336w
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Bovine Serum Albumin and Glucose under Combined High Pressure and Heat

Abstract: The effect of combined heat and pressure on the Maillard reaction between bovine serum albumin (BSA) and glucose was investigated. The effects in the range of 60-132 °C and at 0.1-600 MPa on the lysine availability of BSA were investigated at isothermal/isobaric conditions. The kinetic results showed that the protein-sugar conjugation rate increased with increasing temperature, whereas it decreased with increasing pressure. The reaction followed 1.4th order kinetics at most conditions investigated. A mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…This final section intends to introduce in vitro models of albumin glycation, as a mean to study this phenomenon under controlled conditions. The significant impact of glycation on the protein structure could be observed more conveniently by in vitro techniques such as the use of heat and pressure [108]. HSA has approximately 58 lysine residues [80].…”
Section: Introductionmentioning
confidence: 99%
“…This final section intends to introduce in vitro models of albumin glycation, as a mean to study this phenomenon under controlled conditions. The significant impact of glycation on the protein structure could be observed more conveniently by in vitro techniques such as the use of heat and pressure [108]. HSA has approximately 58 lysine residues [80].…”
Section: Introductionmentioning
confidence: 99%
“…Serum albumins are multifunctional and economically viable due to their extensive use in the pharmaceutical and biotechnological industries (26,27). They are employed as stabilizers in therapeutic proteins, vaccines and enzymes (2830). Serum albumins are amphiphilic in nature and could be utilized to prevent adsorption of other active proteins on the surface of the container, or could be included in the formulation to suppress protein aggregation (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Separately, they are known to have a similar effect on whey proteins: they denature and unfold whey proteins, leading to protein aggregation [6]. Together, pressure and heat were shown to increase, reduce or not affect protein aggregation compared to heat alone, as reported by Buckow et al (2011) and in Chapter 5. Similarly, the combination of heat and pressure affected MR differently in several studies.…”
Section: Hpht Processingmentioning
confidence: 96%
“…Buckow et al (2011) found that protein (BSA) -sugar (glucose) conjugation decreased with increasing pressure during HPHT treatments (0.1-600 MPa, 110°C, 0-50 min, pH 9). They also studied protein unfolding and aggregation.…”
Section: High Pressure -High Temperature Processing Of Protein Systemsmentioning
confidence: 98%
See 1 more Smart Citation